Grammatical Choices and Narrative Quality in the Collaborative Writing of Primary School Students - Cardoso, Inês (2023)
Collaborative writing has been experienced and pointed out as a strong pedagogical tool leading to dialogues when students make their grammar and text choices explicit, discuss and refne their linguistic knowledge within the process. When put into place at an early age, advantages shall increase in what concerns metalinguistic knowledge and the quality of writing. In the present study, we are then putting together different axis related to gram mar and writing learning and teaching. Although no one would doubt that a better text would rely on a wider grammar knowledge and performance, the relation between these language domains isn’t still clear until today in what concerns lan guage teaching. Therefore, we bring to our refection not only the value of metalin guistic knowledge but also the place it has had in our country (in the years of our data collection until today), considering the offcial language teaching guidelines. Not only we will consider grammar but also writing and the pedagogical relation ship recommended offcially. Considering the impact of metalinguistic knowledge in the quality of writing leads us to refect on complex parameters guiding the evaluation of a specifc text, affliated with a particular genre. In the present study, we will be interested then in looking at the development of metalinguistic knowledge in children, by observing their writing process, as well as in assessing the quality of their writing, by observing their written products. The same students were recorded while writing stories in pairs at grades 2 and 4, in the classroom. Data were collected through a multimodal capture system – the Ramos system (Calil, 2020) – which provides us with information of the writing process as well as the written fnal texts. Data samples of this corpus have been selected to study specifc dimensions, such as the elaboration of titles (Barbeiro et al., 2020), lexical density (Costa et al., 2020), the recognition of spelling mistakes (Calil & Pereira, 2018), metalinguistic categories and terms emergent in the writing/revision processes, and how these are (not) translated into textual modifcations, considering the discursive or grammati cal nature of the operations of language re(construction) (Barbeiro et al., 2022; Calil & Myhill, 2020). Now our analysis is focused, on one hand, on the occurrence of metalinguistic terms during collaborative writing; on the other hand, we focused on the textual product, the stories effectively written, measuring their quality in what concerns the compositional aspects of writing narratives in the frst years of schooling. Therefore, we aim to understand better the relationship between a metalinguistic refection and the quality of the text. As Costa and Rodrigues (2019, p. 25) state, “It thus becomes essential to conduct research in at least two felds: research on language development and research on grammar didactics”. The study presented here, following the previous ones men tioned before, is precisely trying to contribute to the feld of grammar-writing articu lation, by trying to apprehend the dimensions of language and texts that are the object of refection and decision, by the same children, in two different moments of their basic schooling (grade 2 and grade 4), during the collaborative writing process of a text: Is grammatical knowledge, namely, using metalinguistic terms (MT), activated during the writing process; in relation to which domains; with what functions; and what impact will children’s “grammatical dialogues” have on the quality of their texts? We will address frst the several theoretical subjects mentioned to pursue with the methodology and analysis of the data considered for this refection, oriented to answer the mentioned questions.